7(1+8n)+7(n+6)=49

Simple and best practice solution for 7(1+8n)+7(n+6)=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(1+8n)+7(n+6)=49 equation:


Simplifying
7(1 + 8n) + 7(n + 6) = 49
(1 * 7 + 8n * 7) + 7(n + 6) = 49
(7 + 56n) + 7(n + 6) = 49

Reorder the terms:
7 + 56n + 7(6 + n) = 49
7 + 56n + (6 * 7 + n * 7) = 49
7 + 56n + (42 + 7n) = 49

Reorder the terms:
7 + 42 + 56n + 7n = 49

Combine like terms: 7 + 42 = 49
49 + 56n + 7n = 49

Combine like terms: 56n + 7n = 63n
49 + 63n = 49

Add '-49' to each side of the equation.
49 + -49 + 63n = 49 + -49

Combine like terms: 49 + -49 = 0
0 + 63n = 49 + -49
63n = 49 + -49

Combine like terms: 49 + -49 = 0
63n = 0

Solving
63n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '63'.
n = 0

Simplifying
n = 0

See similar equations:

| -4x=x-(4x) | | 3y-1+2y=9 | | 16+w*10=-154 | | x^2+25=49 | | 5b*4=30*12 | | -84=-6(p+7) | | -5(p+2)=2(2p-15) | | 3x-9=15-5x | | graphx+y=4 | | 2a+18+26=4a+2 | | -14=n-2-7n | | -24=-4(n-2) | | -3x=3x+12 | | 7a-2=-9+7a | | 12y^2-20y+8=0 | | 4x-2x-5=7 | | 5X+12=4X+26 | | x^2-17x+4900=0 | | C^2+10+9=0 | | 14x+90=162+8x | | 25x-100=75+10x | | 4b-5=-t+5 | | -13=-x-x+7 | | 6x+2x-9=23 | | -24+k=-12 | | 8(3a-5b+6c-7)= | | -16x-4y=28 | | 2+2x+6x=34 | | 4x-6x+7=x-5+12 | | 12-2y=10y-12 | | 8a-11=4a+13 | | (13/15)-(d/5)=(5/6)+(d/3) |

Equations solver categories